Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pengunjung Perpustakaan Di Dinas Perpustakaan Dan Kearsipan - Muhammad Isnaini Fathoni; Yudi Siyamto (Nur Science Institute, 2022)
This study aims to determine the effect of service quality on the satisfaction of library visitors at the library and archives office in Gunungkidul district, Yogyakarta Special Region. This type of research is quantitative research with the aim of proving the effect of service quality variables on visitor satisfaction. The population in this study amounted to 133 people, while the number of samples in this study amounted to 100 people using the slovin formula, the analytical method used in this study was a statistical approach to the type of simple linear regression method with the help of SPSS 23 software. The results of this study indicate that the quality The services provided by the library and archives office in Gunungkidul Regency, Special Region of Yogyakarta, have a significant positive effect on visitor satisfaction, where the magnitude of the influence given is 57.3%, meaning that 42.7% is influenced by other factors that are not used as variables in the study.